Evaluation of antidiabetic activities of Etlingera elatior flower aqueous extract in vitro and in vivo - Nor Asiah Muhamad Nor&, Liza Noordin, Nor Hidayah Abu Bakar, Wan Amir Nizam Wan Ahmad (Journal of Applied Pharmaceutical Science, 2020)
Diabetes mellitus (DM) is a global health problem for millions of people worldwide. Nowadays, medicinal plants have started gaining more attention in diabetes management due to the minimal side effects and cost-effectiveness. This study aims to ascertain the antidiabetic potential of the Etlingera elatior flowers aqueous extract on the in vitro inhibition of carbohydrate digestive enzymes and in vivo type 2 DM rat model. The findings demonstrate that E. elatior flower has a high percentage of inhibitory activity against α-amylase (99.70 ± 2.88%) and moderate activity for the α-glucosidase enzyme (52.39 ± 1.50%). In addition, E. elatior flower has also exhibited an antihyperglycemic effect that is dose-dependent and has significantly decreased the elevated total cholesterol, triglycerides, and low-density lipoprotein levels in the in vivo study. Furthermore, serum creatinine, aspartate aminotransferase, and alkaline phosphatase also were significantly decreased when compared to untreated DM. The high contents of total phenolic (39.06 ± 1.59 mg GAE/g), total flavonoid (39.00 ± 2.42 mg QE/g extract), and potent antioxidant activity were suggested to contribute to the antidiabetic activity of the extract. In conclusion, E. elatior flower could potentially be developed as a natural source of antioxidants that can be used for the prevention or treatment of diabetes.
Keywords: Etlingera elatior, antidiabetic activity, in vitro, in vivo.